Teaching and learning constructive listening skills: A study among EFL learners - Jayanthi Muniandy, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
This article is a report of an action research project conducted in a listening course for EFL students in one of the colleges in Penang, Malaysia. It aims to identify the effectiveness of constructive learning theory in teaching and learning listening skills as the existing teaching practice in the listening course is not rewarding. Four main purposes of listening; comprehensive, critical, appreciative and therapeutic listening were investigated in relation to constructive theory. Young Learners’ Language Strategy Use Survey (YLLS) was conducted to determine the students’ preferred strategies in learning English as a Foreign Language (EFL). Besides, pre-test and post test were employed to identify the efficiency of constructive approachs in teaching and learning listening in EFL classroom. Throughout the entire course, students were observed intently on their involvement in classroom activities. The results from the YLLS questionnaire and classroom observation reveal that listening and speaking become their preferred learning strategy. The findings from pre-test and post-test show EFL learners have improved their listening skills by using constructive approach. In conclusion, constructive listening skills that include prior knowledge, social interaction, motivation and construction of meaning that relate to real world truly help the students to progress in the listening skills. Thus, the college system plays an important role to implement a new listening skills syllabus that contains constructive learning theory to enhance students’ listening skills in English language.